PENGARUH KOMITMEN ORGANISASIONAL, SISTEM INFORMASI AKUNTANSI, DAN PERAN AUDIT INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN - Nugroho, Frasca Ardy; Setyowati, Widhy (ECONBANK: Journal of Economics and Banking, 2019)
This study aims to analyze the effect of organizational commitment, accounting information systems, and the role of internal audit to the quality of the financial statements of Tegal District Government which consists of 150 respondents, data collection methods using questionnaires, data analysis methods using multiple linear regression analysis and data processing using SPSS application. From the results of the partial test, the organizational commitment variable gives a positive and significant effect to the quality of financial statements, as well as the accounting information system variable that gives a positive and significant effect to the quality of financial statements. The third variable, namely the role of the partially internal audit also gives a positive and significant influence on the quality of financial statements. Those variables simultaneously have a positive and significant influence on the quality of financial statements.